2020
DOI: 10.3390/d12070267
|View full text |Cite
|
Sign up to set email alerts
|

Do Habitats Show a Different Invasibility Pattern by Alien Plant Species? A Test on a Wetland Protected Area

Abstract: Biological invasions are deemed to be the second most important global driver of biodiversity loss, right behind habitat destruction and fragmentation. In this study, we aimed at testing if community invasibility, defined as the vulnerability to invasion of a community, could be associated with the characteristics of a given habitat, as described by the composition and structure of its native species. Based on a probabilistic sampling of the alien flora occurring in the temperate wetland Lake Doberdò (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Since ENs are often modeled on the basis of species-habitat interactions and designed based on graph theory [66,67], it is extremely important to join biological data in the graph's early construction stage [44] to confirm the distribution of the habitat types in the area and their composition in terms of plant communities, as they are the primary component for habitat types determination [31][32][33][34] and the basis on which the interaction species-habitat are set up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ENs are often modeled on the basis of species-habitat interactions and designed based on graph theory [66,67], it is extremely important to join biological data in the graph's early construction stage [44] to confirm the distribution of the habitat types in the area and their composition in terms of plant communities, as they are the primary component for habitat types determination [31][32][33][34] and the basis on which the interaction species-habitat are set up.…”
Section: Discussionmentioning
confidence: 99%
“…The sampled EN is composed of numerous PAs and biotopes, as well as several patches of semi-natural and natural habitats in an agricultural landscape matrix. These habitat types, forming the nodes of the EN, consist mainly of wetlands, linked to the presence of rivers and fens, which are well-known for their ecological role and for the high levels of biodiversity [44]. These environments are usually underrepresented in EN studies and the few studies concerning wetlands tend to give more weight to animal diversity instead of plant diversity [45].…”
Section: Introductionmentioning
confidence: 99%
“…Challenging our comprehension of the mechanisms that underlie the invasibility of Invasive Alien Species (IAS) can help us to cope with this key threat to biodiversity [18]. In particular, Tordoni et al [3] suggested that functional niche divergence may foster community invasibility; resident native communities more susceptible to invasion are those which, on average, showed a combination of functional traits (higher resource acquisition capacity and lower drought resistance) coupled with an apparently reduced water-use efficiency.…”
Section: Global Threats and Challengesmentioning
confidence: 99%
“…Smith et al [5] studied the influence of habitat structure and flow permanence on invertebrate community within a karstic spring system; Tanaka et al [6] analyzed macrobenthic invertebrate succession during leaf litter breakdown in perennial karstic rivers in western Brazil. However, regarding karstic ephemeral lakes, most of the studies are focused on vegetation [3,23], productivity [8,13], decomposition processes [10,24] and hydrology [25][26][27].…”
Section: Introductionmentioning
confidence: 99%